Producing 24p Video - Skidgel, John (Routledge, 2012)
Producing 24pP Video demystifies the emerging standards of film and video production and discusses the 24p video film format to help novice and experienced filmmakers alike learn how to better use the newly available DV cameras. Since the 24p frame rate closely approximates the look and feel of film, it is the speed of choice whenever a "cinematic" look is desired. 24p video also offers certain compression options that are advantageous to web and wireless delivery. This full-color book discusses the special techniques required by 24p productions - all the way through the production, from preproduction planning through post and output. Each chapter includes techniques, examples, tips, and case studies. The field techniques section features real-world setups presented as demonstrations or as tutorials. Case studies present profiles of people producing 24p projects, and the DVD includes step-by-step instructions that illustrate how to work with 24p material in NLE, compositor, DVD authoring, and audio applications